Rancang Bangun dan Analisis Opening Bumper Program TV dalam bentuk Motion Graphic (Studi Kasus: Bincang Santai di iNews TV Batam) - Evaliata Br Sembiring; Jonathan Elsson Suhendra; Prasetyo Dharsono; Fadil Mayuheru (Politeknik Negeri Batam, 2021)
Opening Bumper is a short animation opening video in a program that describes the identity of an event or agency. One of the TV programs was